سياسة إعادة تجديد الموجودات الثابتة في منشآت القطاع العام الصناعي في سورية - المهايني, محمد خالد; كفا, ياسر احمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى إيضاح أهمية عملية إعادة تجديد واستبدال الموجودات الثابتة في المنشآت الاقتصادية، نظراً لأهمية الدور الذي يمكن أن تلعبه هذه المنشآت في تحقيق التنمية الشاملة في قطرنا، باعتبارها الوسيلة الوحيدة التي تمكننا من استثمار ثرواتنا الاقتصادية وتحويلها إلى سلع وخدمات تلبي احتياجات ورغبات أفراد مجتمعنا كافة، وعليه فقد تم من خلال هذا البحث تسليط الضوء على جميع المعوقات التي تقف حجر عثرة في سبيل تطوير هذه المنشآت ولاسيما التي تحد من إمكانيتها قي استبدال وإعادة تجديد موجداتها الثابتة التي تعتبر من العناصر المهمة في العملية الإنتاجية وبالتالي عدم قدرتها على تحقيق أهدافها وخططها الإنتاجية والتسويقية...الخ، إضافة إلى تقديم المقترحات التي تُسهم في تذليل هذه المعوقات وتمكن المنشآت من تحقيق أهدافها المنشودة في البناء والتطوير. The aim of this research is to clarify the importance of renewing and replacing fixed assets at economic organizations, because of the important role of these corporations to fulfill comprehensive development in our country, taking into consideration that it is the only way to invest our economic resources and transfer them to commodities and services according to the wishes and needs of persons in our societies, so we highlighted through this research all the obstacles which obstruct the way of developing these corporations especially that which prevent their capabilities in replacing and renewing its fixed assets which are considered an important element in the production process, so its inability to fulfill its production and marketing aims and plans…etc, in addition to submitting suggestions which may delete these obstacles and make these corporations fulfilling its aims in building and developing